Inner structure and inclusions in radiocesium-bearing microparticles emitted in the Fukushima Daiichi Nuclear Power Plant accident. (5th February 2019) - Okumura, Taiga; Yamaguchi, Noriko; Dohi, Terumi; Iijima, Kazuki; Kogure, Toshihiro
Abstract : Radiocesium-bearing microparticles, which were released from the damaged reactors to the environment during the Fukushima nuclear accident, were investigated by transmission electron microscopy. The detailed investigations of their inner structures and inclusions offer information on the reactors that are difficult to access because of the high radiation fields. Abstract: Radiocesium-bearing microparticles (CsMPs), consisting substantially of silicate glass, were released to the environment during the Fukushima Daiichi Nuclear Power Plant accident in March 2011. Since the CsMPs were formed inside the damaged reactors during the accident, we investigate the inner structures of several CsMPs by transmission electron microscopy to understand the events within the reactors. Elemental mapping of the CsMPs shows a distinct radial distribution of Cs with a higher concentration near the surface of the CsMPs, implying that Cs was in a gaseous state in the reactor atmosphere and diffused into the glass matrix after formation of the glass particles. In some CsMPs, Zn and Fe also showed a similar radial distribution to Cs, suggesting that those elements may have diffused outward where Cs was abundant. In addition, submicron crystals were present as inclusions in several of the CsMPs and were identified as chromium spinels ((Fe 2+, Zn)(Cr, Fe 3+ )2 O4 ), acanthite (Ag2 S), molybdenite (MoS2 ) and hessite (Ag2 Te). The spinels contained ferrous iron (Fe 2+ ), suggesting that the atmosphere inside the reactors was reductive to some extent. Also, boron was not detected in the glass matrix of the CsMPs despite using electron energy-loss spectroscopy, indicating that most of the control rods made of B4 C might have created a eutectic alloy without vaporization. These detailed investigations of the inner structures in the CsMPs may offer information on the damaged reactors that are difficult to access because of the high radiation fields.